Long‐term outcomes associated with the transaortic approach to transcatheter Aortic valve replacement. Issue 7 (3rd February 2015) - Lardizabal, Joel A.; Macon, Conrad J.; O'Neill, Brian P.; Desai, Harit; Singh, Vikas; Martinez, Claudia A.; Alfonso, Carlos E.; Cohen, Mauricio G.; Heldman, Alan W.; O'Neill, William W.; Williams, Donald B.
<x xml:space="preserve">Abstract</x> Objective We investigated the long‐term safety, efficacy and clinical outcomes associated with transaortic (TAO) transcatheter aortic valve replacement (TAVR) in the United States. Background We previously reported the technical feasibility and short‐term safety of TAO TAVR. Compared to transapical (TAP) access, the TAO approach was associated with shorter median intensive care unit (ICU) length of stay (LOS) and more favorable technical learning curve. However, outcomes data beyond 30 days were lacking and the longer‐term clinical consequences of this strategy were unknown. Methods Mortality outcomes at 1 year (and longer) of 44 consecutive patients who underwent TAO TAVR in our institution were compared with that of 76 consecutive patients who underwent TAP TAVR at our site. Risk‐adjusted analysis was performed in propensity‐matched patients (25 from each group) to account for baseline differences. Results TAO TAVR was associated with a trend towards lower all‐cause mortality at 1 year compared to TAP TAVR (18% vs. 34%, P=0.09 in the overall sample; 12% vs. 40%, P = 0.05 in the matched cohort). The higher probability of survival with TAO TAVR persisted after a median follow‐up period of 23 months (hazard ratio [HR]=1.96, P = 0.06 in the overall sample; HR = 3.4, P = 0.01 in the matched cohort). Cardiovascular mortality at 1 year was lower with TAO TAVR (2% vs. 22%, P = 0.01 in the overall sample; 4% vs. 28%, P = 0.05 in the matched cohort). ICU LOS (shorter in the TAO group) and implantation of second prosthetic valve (higher incidence in the TAP group) were independent predictors of long‐term mortality. Conclusion The outcomes associated with TAO TAVR compare favorably with TAP TAVR. Our results appear to corroborate the long‐term safety and efficacy of the TAO approach in TAVR patients with inadequate iliofemoral access. © 2015 Wiley Periodicals, Inc.